EFFICIENCY OF USING OPTIMIZATION METHODS IN LOGISTICS PROBLEMS - ZAKHARCHENKO, RAISA; RASTORGUYEV, VYACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article comprehensively researches the theoretical and applied aspects of the application of optimization methods in logistics systems. Modern mathematical approaches to solving logistics problems are analyzed, their effectiveness and potential for increasing the economic performance of enterprises is determined. Mathematical models, optimization techniques and practical recommendations for the implementation of optimization technologies in logistics processes are considered.The current state of development of the world economy is characterized by a high level of competition and constant changes in the market environment. In such conditions, the efficiency of logistics systems becomes a critically important factor in the success of enterprises. Optimization of logistics processes allows you to significantly reduce costs, increase the speed and quality of service, as well as ensure the flexibility and adaptability of business processes.Logistics is a key element of modern business that ensures effective management of material and information flows. In order to increase the competitiveness of enterprises, optimization methods become important tools for improving logistics processes. This study is devoted to the analysis of the effectiveness of the use of various optimization methods in logistics tasks, in particular in inventory management, transportation and planning.The relevance of the study is determined by the following factors: growing complexity of logistics systems; the need to implement optimization methods for managing logistics systems; the need to increase the economic efficiency of enterprises in the conditions of war; development of logistics in the organization of transport and passenger transportation in wartime conditions.
Keywords: optimization methods; information technologies; logistics; logistics systems; transportation organization